METODE ITERASI TIGA LANGKAH DENGAN KEKONVERGENAN BERORDE ENAM BELAS - Ricko Saputra; Supriadi Putra; Agusni ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses a new method for finding roots of nonlinear equations. The process of forming the new method is derived from combining Newton’s method and King’s method with b= -0.5. Error analysis performed on the new method shows that it has a convergence of order sixteen. Numerical examples are compared to Newton’s method, King’s method, and the new method.